2008
DOI: 10.1007/s11745-008-3215-0
|View full text |Cite
|
Sign up to set email alerts
|

Stearidonic Acid‐Enriched Soybean Oil Increased the Omega‐3 Index, an Emerging Cardiovascular Risk Marker

Abstract: A plant source of omega-3 fatty acid (FA) that can raise tissue eicosapentaenoic acid (EPA) and/or docosahexaenoic acid (DHA) is needed. A soybean oil (SBO) containing approximately 20% stearidonic acid [SDA; the delta-6 desaturase product of alpha-linolenic acid (ALA)] derived from genetically modified soybeans is under development. This study compared the effects of EPA to SDA-SBO on erythrocyte EPA+DHA levels (the omega-3 index). Overweight healthy volunteers (n=45) were randomized to SDA-SBO (24 ml/day pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(135 citation statements)
references
References 31 publications
10
123
1
1
Order By: Relevance
“…Krul et al report no effect of consuming different amounts of SDA (0.43, 1.3, 2.6 or 5.2 g/d) from this oil for 12 weeks on plasma cholesterol or TAG concentrations in healthy male and female subjects [100]. Harris et al also found no change in serum cholesterol or TAG concentrations after consuming of 3.7 g/d SDA from SDA-rich soybean oil for 16 weeks in overweight or obese adults [166]. Another study reported no change in serum cholesterol concentration after consuming 4.2 g/d SDA for 12 weeks, although there was a nonsignificant trend (9% decrease) towards lower TAG concentration [98].…”
Section: Alpha-linolenic and Stearidonic Acids And Cardiovascular Rismentioning
confidence: 99%
“…Krul et al report no effect of consuming different amounts of SDA (0.43, 1.3, 2.6 or 5.2 g/d) from this oil for 12 weeks on plasma cholesterol or TAG concentrations in healthy male and female subjects [100]. Harris et al also found no change in serum cholesterol or TAG concentrations after consuming of 3.7 g/d SDA from SDA-rich soybean oil for 16 weeks in overweight or obese adults [166]. Another study reported no change in serum cholesterol concentration after consuming 4.2 g/d SDA for 12 weeks, although there was a nonsignificant trend (9% decrease) towards lower TAG concentration [98].…”
Section: Alpha-linolenic and Stearidonic Acids And Cardiovascular Rismentioning
confidence: 99%
“…With respect to SDA-and GLA-rich oils, no adverse effects were found on the concentrations of blood lipids, blood pressure, heart rate, platelet function, standard blood laboratory tests and adverse events recording in studies using SDA-rich soybean oil (doses of 3 700 mg SDA/day plus 1 200 mg GLA/day for 16 weeks and 4 200 mg SDA/day plus 1 100 mg GLA/day for 12 weeks) (Harris et al, 2008;Lemke et al, 2010) or Echium oil (doses of 1 900 mg SDA/day plus 1 700 mg GLA/day for 28 days and 1 000 mg SDA/day plus 900 mg GLA/day for 12 weeks) (Miles et al, 2004b;Miles et al, 2004a;Surette et al, 2004;Miles et al, 2006).…”
Section: Human Studiesmentioning
confidence: 95%
“…Efficiencies of conversion of SDA to EPA of between 3:1 and 6:1 have been reported, as measured by changes in the percentage of EPA in erythrocytes (James et al, 2003;Harris et al, 2008;Lemke et al, 2010).…”
Section: Absorption Distribution Metabolism and Excretionmentioning
confidence: 99%
“…Most evidence for benefits apply to the -3 LCFAs. Considering this, two problems are indicated: western diets are typically low in EPA and DHA because consumption of the primary source of these fatty acids from oily fish (such as salmon, mackerel, albacoretuna, and sardines) is low (Harris, Lemke et al 2008) and it is problematic to recommend to patients or the community to increase fish intake due to price and availability of oily fish (James, Ursin et al 2003). Because conversion of dietary ALA into EPA is limited and a fish/fish oil based diet is not easily adopted, dietetic solutions to this limitation should provide great perspectives for the future.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The efficiency of ALA conversion into EPA was shown to be 0.09%, while SDA conversion was 16.6% (relative to EPA). Hence, another strategy for raising tissue EPA levels with a plantbased -3 is to consume foods containing SDA (Harris, Lemke et al 2008). James et al (2003) showed greater enrichment of EPA in plasma and lipid cells if subjects supplemented their diet with ethyl ester of SDA than if supplemented with the same amount of the ethyl ester of www.intechopen.com ALA.…”
Section: Future Perspectivesmentioning
confidence: 99%